Енергетична безпека в умовах геополітичної нестабільності - Яковюк, І. В.; Єфремова, К. В.; Новіков, Є. А. (НДІ ПЗІР НАПрН України, 2022)
Питання енергетичної безпеки є одним із наріжних каменів енергетичної політики США, Європейського Союзу та багатьох інших держав, зокрема України. Російсько-українські конфлікти, що почалися з 2006 р., у фазах свого найбільшого загострення (2014 та 2022 роки) суттєво впливають на постачання газу, які мають вкрай негативний вплив на функціонування ЄС та перешкоджають реалізації курсу на глобальний енергетичний перехід до низьковуглецевої економіки. Концепція енергетичної безпеки досліджувалась різними авторами і, хоча щодо її змісту немає єдиної думки (на неї впливають такі фактори як глобалізація, енергетична і геополітична нестабільність, взаємозалежність між енергетичною безпекою та змінами клімату, а також волатильність цін), вона має важливе значення як для окремої держави, так і регіонів, зокрема Європи. Оптимальною слід вважати розширену концепцію енергетичної безпеки, яка базується на трьох аспектах: суверенітет, надійність та стійкість. Газова криза, яка на перший погляд є суто політичним питанням, насправді завжди також включає й економічний елемент, оскільки завдає економічної шкоди іншим країнам. Через російсько-українську війну і її наслідки перед європейськими країнами постав виклик щодо того, як переосмислити парадигму енергетичної безпеки у зв’язку із необхідністю звільнитися від енергетичної залежності від Москви і при цьому не підірвати імператив енергетичного переходу на всьому континенті. Стаття є внеском у дослідницький порядок денний з питань критичної енергетичної безпеки, а також літературу, спрямовану на дослідження взаємозв’язку між енергетикою та національною ідентичністю. Problem setting. Energy is the main resource, and therefore acts as an object of strategic interest and policy. There are many uncertainties in modern energy governance, as it is influenced by many political positions that have different approaches to how best to achieve the desired future and avoid undesirable developments in the energy market. The energy transition should be recognised as one of the main pressures that increasingly complicate and restructure energy supply pathways. The shifts it generates are not only purely technical, but also social, conceptual and political. Obviously, energy supply is in some way linked to national identity, the position a state takes in international relations, and technological development. However, as energy markets and resource supply chains are becoming increasingly global, national approaches to energy security (security of supply) are responding to international developments, in particular the Russian aggression against Ukraine, to varying degrees. Аnalysis of resent researches and publications. In the scientific literature, energy security, as well as energy sovereignty, are defined differently, since there is no clear consensus among researchers on these phenomena, but there are some dominant approaches. Over the past decade, domestic authors have devoted a lot of attention to the study of the conflict of ensuring energy security of Ukraine in the context of the need to make geopolitical choices. However, the problem of ensuring energy security in martial law and the post-war period is only being raised in scientific research, which determines its relevance. The target of the research is to determine the priority directions of energy policy to improve energy security based on the analysis of the problems of functioning of national energy security systems, as well as current threats to vital national interests in this area. Article’s main body. The issue of energy security is one of the cornerstones of the energy policy of modern states. The Russian-Ukrainian conflicts that began in 2006, in the phases of their greatest aggravation (2014 and 2022), significantly affect gas supplies, which have a very negative impact on the functioning of the EU and impede the implementation of the course of the global energy transition to a low-carbon economy. The concept of energy security has been studied by various authors and, although there is no consensus on its content, it is important for both individual states and regions, in particular Europe. An expanded concept of energy security based on three aspects should be considered optimal: sovereignty, reliability and sustainability. Conclusions and prospects for the development. An indicator of the effectiveness and balance of the national energy strategy is the moderate dependence of the state on imports of foreign energy resources. From the point of view of economic security, there is a need to build a balanced diversified structure of energy imports to avoid dependence (dictate) on individual exporting countries. The imbalance of foreign economic strategy in the energy sector is one of the reasons for the acute energy crisis in most European countries. The energy-related causes of the crisis are the inability of most states to significantly reduce energy consumption and increase the innovative component of technological renewal of the fuel and economic complex. Prevention of such crises requires a transition from the traditional paradigm of ensuring economic growth through the import of cheap energy to the strategy of energy saving and increasing the use of renewable energy sources, which is in line with the principles of sustainable development.
Keywords: економічна безпека; суверенітет; енергетична політика; енергетичне домінування; енергетична незалежність; ресурсний націоналізм; енергетична справедливість; economic security; sovereignty; energy policy; energy dominance; energy independence; resource nationalism; energy justice